Orange peel ethanolic extract and physical exercise prevent testicular toxicity in streptozocin and high fat diet-induced type 2 diabetes rats via Nrf2/NF-kB signaling: In silico and in vivo studies - Adeyemi Fatai Odetayo; Ayodeji Johnson Ajibare; Kazeem Bidemi Okesina; Tunmise Marryane Akhigbe; Ezekiel Abiola Olugbogi; Luqman Aribidesi Olayaki (Heliyon)
Background: Type 2 diabetes mellitus (T2DM) is a significant health issue affecting the quality of life including male reproductive functions. Orange peel ethanolic extract (OPEE) has been established to have antioxidant properties and has been shown to alleviate diabetic complications. This study determined to establish OPEE effect and physical exercise (EX) in T2DM-induced testicular dysfunction. Materials and methods: Thirty male Wistar rats were randomly distributed in five groups as follows: control group (received 1 ml/b.w of normal saline), and groups 2–5 were induced with diabetes, with group 2 left untreated, group 3 received 600 mg/kg b.w OPEE, group 4 was subjected to EX while group 5 was treated with OPEE alongside EX. Results: OPEE + EX ameliorated T2DM-induced decrease in sperm motility, count, and morphology and increased testicular lactate dehydrogenase, alkaline phosphate, gamma-glutamyl transferase, and lactate. T2DM-induced disruption of gonadotropin-releasing hormone, luteinizing hormone, follicle-stimulating hormone and, testosterone was also mitigated by OPEE + EX. In addition, OPEE + EX blunted T2DM-induced increase in oxidative stress, inflammatory, and apoptotic markers and the accompanied decrease in testicular nuclear factor erythroid 2–related factor 2 (Nrf2) and increase in nuclear factor kappa B (NF-κB). Also, OPEE + EX reversed T2DM-induced testicular histology distortion. Conclusions: The outcome of this study revealed that the combination of OPEE and EX ameliorated T2DM-mediated testicular damage via Nrf2/NF-κB signaling.